Desegregation State : College Writing Programs after the Civil Rights Movement - Mendenhall, Annie S. (Book collections on Project MUSE., 2022)
"A history of federal enforcement of higher education desegregation and its impact on writing programs. Focusing on University System of Georgia and two colleges, one a historically segregated white college and a historically Black college showing desegregation enforcement promoted and shaped writing programs by presenting literacy remediation and testing as critical to desegregation"--